Ato administrativo de concessão de benefício - Nascimento, Ricardo de Castro (2006)
The objective of this dissertation is the study of the practices in the management of the social security by the public service. We begin by analyzing the main characteristics of the administrative function, from the various points of view under the perspectives of the national and foreign doctrines, and through the history of social security as a function of the state. We describe the peculiarities of the public service of social security, the major objective of which to provide social protection according to the law is embodied and characterized legally through an administrative act. We present a list of the main characteristics of the administrative act, its elements, and the vices that can invalidate it. The study of the peculiarities of the administrative act for granting benefits is the next step. We also analyze the demand to present an initial application for the benefit, as well as the duty-power of decision of the social security administration and the legal consequences of its inaction or silence. Finally, we examine the virtual administrative act, through which the benefits will be granted in the future